The effect of psychodrama on quality of life and sleep in mothers of children with cerebral palsy. (February 2021) - Simsek, Caglar; Mengi, Alper; Yalcinkaya, Ebru Yilmaz
Highlights: Having a child with disability may affect the caregiver physically and mentally. Psychodrama is a method that can be used in mothers of children with cerebral palsy. Psychodrama may have a positive effect on the quality of life of mothers. Abstract: The different conditions such as impaired sleep quality, impaired quality of life and decreased psychological health have been reported in caregivers of children with disabilities. It was aimed in this study to determine if psychodrama intervention causes any change on the sleep and life quality of mothers of children with cerebral palsy. Psychodrama intervention in sessions of 2 h a week for 8 weeks was applied to psychodrama group, and the study was completed with 8 mothers in the psychodrama group and 14 mothers in the control group. The mothers were evaluated in terms of sleep quality assessed by Pittsburgh Sleep Quality Index (PSQI) and quality of life assessed by Short Form-36 (SF-36) before the treatment and at the end of the 8th week. The clinically significant improvements were detected in all SF-36 subscale scores in the psychodrama group compared to the control group, only score of bodily pain subscale showed a statistically significant percentage change. There was no difference between the groups in the percentage change in PSQI scores. This study has shown that psychodrama intervention had no effect on sleep quality while it might have clinically positive effects on all of the quality of life subscales.